Fairy Tail. 60 - Mashima, Hiro, 1977- (Kodansha Comics, 2017)
"Amidst the bloodshed of the final battle, Natsu suddenly transforms -- he becomes trappedin the depths of his own heart, wading through his lost memories..." -- Back cover.